Stalin era intellectuals : culture and Stalinism - Viljanen, Elina; Oittinen, Vesa, 1951- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book focuses on the extent to which Soviet scholars and cultural theoreticians were able to act autonomously during the Stalin era. The authors question how we should consider certain intellectual achievements which took place despite the pressure of Stalinism, and how best to recognise and describe such achievements. The chapters offer suggestions for new interpretations on Soviet philosophy of science and humanities, linguistics, philosophy, musicology, literature and mathematics from the point of view of general cultural theory. In this way, they challenge the received image of the Stalin-era humanities which reduces them into mere propaganda. Intended for scholars of Russian and Soviet studies this book will dispel many received views about the character of Stalinism and Soviet culture"--
On Soviet Intellectual Culture during the Stalin Era / Vesa Oittinen and Elina Viljanen -- Fighting Avant-Garde with Phenomenology : Gustav Shpet's 'New Realism' / Liisa Bourgeot -- The Concept of 'Menshevising Idealism' and the Stalinisation of Soviet Philosophy / Vesa Oittinen -- The Naked Truth of Fact : Andrey Platonov on the Margins of Factography / Maria Chehonadskikh -- Everyday Symphonism : Boris Asafiev's Soviet Theory of Popular Music / Elina Viljanen -- Confronting Modernism in the Stalin Era : Mikhail Lifshits as Critic and Philosopher of Culture / Sascha Freyberg -- Maxim Gorky as Spokesman for Proletarian Humanism / Jutta Scherrer -- Sofya Yanovskaya in Defence of Abstractions : Between Soviet Ideology and Bourgeois Idealism / Tatiana Levina -- The Anti-Fascist Cultural Theory of Nikolai Bukharin and the Concept of Socialist Humanism / Vesa Oittinen and Elina Viljanen -- Nikolay Marr's Theory of Language and Konstantin Megrelidze's Historical Science of Thought / Elene Ladaria -- Between Critique and Conformism : The Languages and Cultures of Caste and Nation in Stalin-era Indology / Craig Brandist -- Stalin and Philosophy in Soviet Russia / Marina F. Bykova -- Stalinism, War, and Artistic Representation of Reality : Konstantin Simonov's Critique of the 'System of Silence' in 1956 / Susan Ikonen.
Keywords: Intellectuals -- Soviet Union; Politics and culture -- Soviet Union; Philosophy, Russian -- 20th century; Soviet Union -- Intellectual life; POLITICAL SCIENCE / General